Corporate Sustainability Reporting And Firm Performance Linkage-A Literature Review Approach - Sreepriya Jayakumar, Suprabha K R (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
The study uses a bibliometric approach to map the developments in the area of corporate sustainability reporting and firm performance relation. A sample of 96 articles extracted from Scopus database is used for attaining an overview regarding this relationship. The review will help the business in policymaking as well as in strategizing their sustainability reporting and sustainability initiatives. The study will help the investor in assessing the impact of a non-financial factor in firm performance for making a better decision in the investment. VOS viewer is used in extracting general information regarding sustainability reporting and firm performance relation. The paper found, healthy growth in the number of publications in the field of sustainability reporting and firm performance moreover its evolving especially in Indian context. The paper also found that further understanding of this relationship will aid academia and scholars for exploring the unidentified area in this field.